2015
DOI: 10.1007/s12275-015-5348-1
|View full text |Cite
|
Sign up to set email alerts
|

Innate signaling mechanisms controlling Mycobacterium chelonae-mediated CCL2 and CCL5 expression in macrophages

Abstract: Mycobacterium chelonae (Mch) is an atypical rapidly growing mycobacterium (RGM) that belongs to the M. chelonae complex, which can cause a variety of human infections. During this type of mycobacterial infection, macrophage-derived chemokines play an important role in the mediation of intracellular communication and immune surveillance by which they orchestrate cellular immunity. However, the intracellular signaling pathways involved in the macrophage-induced chemokine production during Mch infections remain u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…NF-κB is a vital immune regulator, which can be activated by RIG-I signaling and activates the transcription of a large array of cytokines and other immune genes, such as NOS2 [62,63,64]. In the present work, we observed that the phosphorylation level of NF-κB p65 was decreased upon live versus dead E. tarda infection, indicating a suppression of NF-κB activity by live E. tarda .…”
Section: Discussionsupporting
confidence: 54%
“…NF-κB is a vital immune regulator, which can be activated by RIG-I signaling and activates the transcription of a large array of cytokines and other immune genes, such as NOS2 [62,63,64]. In the present work, we observed that the phosphorylation level of NF-κB p65 was decreased upon live versus dead E. tarda infection, indicating a suppression of NF-κB activity by live E. tarda .…”
Section: Discussionsupporting
confidence: 54%
“…However, the mechanism/s and correlates of protection of these responses during the various stages of this chronic disease are not understood. Other studies in the mouse models or murine cells models of NTM infection have shown the importance of CCL2, CCL5, and TLR signaling via MAPK, MyD88, and NFκβ for disease protection (86)(87)(88). Robust mouse models for M. avium infection exist though currently, it is difficult to initiate infection, maintain infection, and measure immune responses in MABS mouse models (89,90).…”
Section: The Immune Response In Pulmonary Ntm Infectionmentioning
confidence: 99%